TRAINING ON DIGITAL TEACHING MATERIALS TO IMPROVE STORYTELLING AND WRITING SKILLS: BOOK CREATOR AND SEESAW - Lisa Anna Nasution Lisa; Nurwulan; Is Mardis; Nuril Huda; M. Fikri Yusuf; Apriyanti Tsaniatun Nisa (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to improve the competence of elementary school teachers in using interactive digital media, such as Book Creator and Seesaw. This activity was motivated by various problems, including students' difficulties in developing story ideas, choosing vocabulary, and understanding narrative structure, which impacts low writing motivation. Furthermore, teachers' readiness to integrate digital technology is still limited, and support from the education system and infrastructure is not optimal. The method used was PAR (Participatory Action Research), which was implemented in KKG Cluster 3 Citaringgul, Bogor Regency, involving 15 teachers through three stages: needs analysis, training and mentoring, and reflective evaluation. The results showed an increase in teachers' skills in designing digital media with an average score of 3.6 (good category). Teachers were also able to produce engaging, interactive digital books. This activity encourages the formation of a digital literacy culture and an ICT-based community of practice.